Activity trypsin-like proteinases and intestinal mucosa collagen degradation at gastro-intestinal diseases - О. E. Akbasheva; V. A. Burkovskaya; A. E. Dehand; E. I. Beloborodova; L. A. Akimova; E. L. Naumova; E. A. Kvach (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To determine activity of trypsin-, collagenase- and elastase-like proteinases, a1- proteinase inhibitor, a2-macroglobulin and contents of hydroxyproline in intestinal mucosa and blood plasma of patients with bowel diseases.Material and methods. Sixty patients with ulcerative colitis, 42 – with Crohn’s disease, 18 - with irritable bowel syndrome and 30 practically healthy persons were investigated. A supernatant, obtained from biopsy specimens of intestinal mucosa, was used for assessment of biochemical parameters. Activity of trypsin-like proteinases was estimated by hydrolysis of synthetic substrate N-benzoyl-L-arginine ethyl ester (BAEE). Activity of a1-proteinase inhibitor (a1-PI) and a2-macroglobulin (a2-MG) was determined by unified method on of BAEE hydrolysis inhibition. A degradation of fibrous proteins of connective tissue was estimated by activity of elastase- and collagenase-like proteinases and by the contents of hydroxyproline fractions. Activity of elastase- and collagenase-like proteinases was determined, using N-butoxycarbonyl-L-alanine p-nitrophenyl ester (BANE) as substrate.Results. Activation of proteolysis in mucosa of intestine and blood plasma of patients on a background of decrease of activity of proteinase inhibitors and elevation of hydroxyproline contents was revealed. Changes were most severe at Crohn’s disease in comparison to ulcerative colitis and irritable bowel syndrome. At ulcerative colitis along with increase of severity grade activity of trypsin-, elastase-like proteinases and level of free hydroxyproline of intestinal mucosa increased. By logistical regression method it was calculated, that deficiency of a2-MG increases the risk of Crohn’s disease development 3,85 times.Conclusion. At ulcerative colitis and Crohn’s disease in mucosa of intestine activation of trypsin-, elastase- and collagenase-like proteinases on a background of decrease of activity of a1-PI and a2-MG that results in degradation of connective tissue proteins is observed. The most severe disorder of collagen and elastin metabolism, i.e. substantial increase of collagen decomposition products, proteinases activity on the background of deficiency of inhibitors in mucosa of intestine and blood plasma occurs in Crohn’s disease.